Pengembangan “History Book” Berbasis Hypermedia untuk Kelas IV Materi Peninggalan Sejarah di Pulau Jawa - Waridah, Ni’matu; Cholifah, Puri Selfi; Khotimah, Khusnul (Magister Pendidikan Dasar FKIP Universitas Mataram, 2025)
The purpose of this study is to develop a hypermedia-based “History Book” learning media on historical heritage materials during the Hindu, Buddhist, and Islamic times on the island of Java for the fourth grade of elementary school. The limitations of learning media result in the learning process that will be carried out by the teacher being less than optimal, so that it has an impact on the level of student understanding regarding the material. The development of interactive learning media and according to the characteristics of elementary school students who prefer colorful, practical learning media equipped with pictures, videos and worksheets that can be done directly is very necessary. The model used in this study is a research and development model of the ADDIE type, which consists of 5 stages. namely analysis (analysis), design (design), development (development), implementation (implementation), and evaluation (evaluation). Based on the results of the study, it was found that the History Book was very valid, very interesting and very practical so that it was feasible to use. The average validation results from material experts and media experts are 89.6% and are categorized as very valid, while product practicality tests by practitioners get an assessment of 95% with very practical categories. The practicality of the product from the students got an average score of 97.33% in the very practical category, while the attractiveness of the product got an average score of 99.58% from the students in the very attractive category. This History Book learning media can be used by students with high, medium, and low abilities and provide additional knowledge and insight related to historical heritage materials from the Hindu, Buddhist and Islamic eras on the island of Java.